Factory-on-chip: Robust simulation-driven optimization design of modular microfluidic chip array for functional materials performance control and high-throughput synthesis - Yu, Qifan; Qi, Menghua; Zhang, Cheng; Zhang, Li; Wang, Bingjie (Chemical engineering journal (Lausanne, Switzerland : 1996), 2025)
Limited by the bottleneck issues of low integration, non-modularization and high processing cost of microfluidic chips, droplet microfluidic technology is difficult to achieve an effective balance between the performance control and high-throughput synthesis of high-performance functional materials. As a result, this technology still remains in the laboratory research stage, which seriously restricts its industrial application prospects. In this study, the design criteria for uniform fluid distribution of the tree branching structure with flow resistance-error compensation mechanism was unprecedentedly proposed. Based on CFD numerical simulation, the minimum length of the serpentine channel that satisfied the uniform distribution condition was calculated. Besides, the primary amplification structure with central inlet and the secondary amplification structure with branch angle of 120° were confirmed. And then, a 10-layer modular microfluidic chip array (MMCA) composed of 12-channel, two-stage annular tree branching amplification structure microfluidic chips was developed. Through precise regulation of formation pattern and particle size, highly monodispersed chitosan adsorbents were batch prepared, with an average particle size of 586 μm, a CV value as low as 2.61 %, and a yield as high as 2100 mL/h. The prepared chitosan adsorbent exhibited excellent adsorption performance for heavy metal ions and azo dyes. The corresponding saturated adsorption capacities reached 78 mg/g and 184 mg/g, respectively, and the equilibrium time was shortened to within 7 h. This study can provide theoretical support for the modular design and low-cost processing of microfluidic parallel amplification systems. [Display omitted] •The design criteria for uniform fluid distribution of tree branching structure was proposed.•A 10-layer MMCA with 12-channel, two-stage amplification structure was developed.•The minimum lengths of the serpentine channels for two-stage amplifications were 99.14 and 55.56 mm.•The CV of the prepared chitosan adsorbent was only 2.61 %, and the yield was up to 2100 mL/h.•The adsorption capacities for Cu ions and MO molecules reached 78 mg/g and 184 mg/g, respectively.